2012
DOI: 10.1080/10942912.2010.487625
|View full text |Cite
|
Sign up to set email alerts
|

Influence Of Age On Red Wine Colour During Fining With Bentonite And Gelatin

Abstract: Two fining agents (bentonite and gelatin) have contributed to the reduction of colour of Pinot Noir wine of different ages. Bentonite caused more significant changes in the colour of young wines. Colour intensity, coloured anthocyanin forms, and polymers were reduced to a greater extent, while colourless anthocyanins and total phenolic substances were reduced to a lower extent. Smaller changes in coloured substances resulted from wine treatment with gelatin. The intensity of the share of yellow colour decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 11 publications
(9 reference statements)
4
24
3
Order By: Relevance
“…() on wines with 2‐month age. Similar results were observed in red wines aged for a longer period of time (Stankovic et al ., ) than the Valpolicella wine under study. Differently to our results (Table ), Tománková et al .…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…() on wines with 2‐month age. Similar results were observed in red wines aged for a longer period of time (Stankovic et al ., ) than the Valpolicella wine under study. Differently to our results (Table ), Tománková et al .…”
Section: Resultsmentioning
confidence: 90%
“…Likewise to what reported by Stankovic et al . (), Tománková et al . () found that the addition of 1.00 g L −1 bentonite was necessary to reduce anthocyanins by 23–26%.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations